A Review on Potential Activities of Different Parts of Cassia sophera as Antidiabetic, Antimicrobial and Anticancer Agent - Chakraborty, Atyurmila; Acharjya, Sasmita K.; Tripathy, Bimala; Shree, Dipthi (Anti-Infective Agents, 2022)
Background: Herbal medicines are one of the giant creations of nature. Several medicinal agents developed from natural sources, which open a new era of health sciences. Cassia sophera is a prevalent medicinal plant that is locally known as “Kasondi”, belonging to the family Caesalpinaceae. Many secondary metabolites like alkaloids, tannins, anthraquinones, flavonoids are isolated from roots, stems, leaves, flowers, and seeds of C. sophera, which are very effective against several diseases. Objective: Cassia sophera has an enormous potential in public health to protect from diabetes, microbes, and cancer. Hence, the aim of the present review is to collect the reported antidiabetic, antimicrobial, and anticancer activity of Cassia sophera along with a detailed discussion about mechanism of action of various phytoconstituents. Discussion: Antidiabetic activity of Cassia sophera is due to the activation of β cell and stimulation of surviving pancreatic β-cells to release more insulin. Plasma membrane disruption, inhibition of cell wall formation, inhibition of cell division by the Cassia sophera is the prime causes of antimicrobial activity. The anticancer activity of the plant is mainly due to the prevention of reactive oxygen species formation, induction of cell cycle arrest, apoptosis, and angiogenesis. Conclusions: The findings from this review article confirm the potential activities and mechanisms of various phytoconstituents responsible for preventing diabetes, cancer, and microbial infections. Further investigation regarding possible pharmaceutical side effects, contraindications, drug interactions involving drugs synthesized from C. sophera should be carried out by the researchers.
Keywords: Cassia sophera